2007
DOI: 10.3201/eid1307.060773
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis, Sri Lanka

Abstract: Cutaneous leishmaniasis (CL) is an emerging disease in Sri Lanka. Of 116 patients with clinical symptoms suggestive of CL, 86 were confirmed positive for Leishmania donovani. Most patients had single dry lesions, usually on the face. Patients were from 5 of the 7 agroclimatic zones in Sri Lanka.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 13 publications
6
47
1
Order By: Relevance
“…Therefore, this may not be a direct suggestion of zoonotic transmission, rather a peri-domestic nature of transmission, and is in contrast to the findings of the previously conducted studies in Northern Sri Lanka. [24][25][26] Since peri-domestic environment appears to be associated with L. donovani transmission, further spread of infection within Sri Lanka might be unavoidable under present circumstances. Early detection and treatment of patients would therefore, considerably help to contain the situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this may not be a direct suggestion of zoonotic transmission, rather a peri-domestic nature of transmission, and is in contrast to the findings of the previously conducted studies in Northern Sri Lanka. [24][25][26] Since peri-domestic environment appears to be associated with L. donovani transmission, further spread of infection within Sri Lanka might be unavoidable under present circumstances. Early detection and treatment of patients would therefore, considerably help to contain the situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were limited due to their restricted geographical coverage and the small size of the population covered. With reference to the aforementioned studies, zoonotic transmission was suspected in the Northern parts of the country, during the early stages of the outbreak, [20][21][22][23][24][25] with gender (male), age (between 21 and 40 years) and outdoor occupation as risk factors. The traditional view of anthroponotic L. donovani transmission has been challenged with some evidence pointing towards the presence of animal reservoirs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that CL lesions are generally seen on uncovered parts of the body and less often on covered areas. 1,14,[20][21][22][23][24] This is not surprising since these are the areas that are readily accessible by the sandfly. A study in Turkey by Gurel and others 9 reported the location of CL lesions as 57.5% in the head and neck region, 32.2% in the upper extremities, 10.2% in the lower extremities, 0.8% in oral mucosa, 0.2% on the trunk, and no mucosal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…1 About 350 million people in 98 countries are at risk of CL, making it a significant public health problem. 2 Based on the causative species and geographical distribution of the disease, CL is divided into Old World CL (southern Europe, the Middle East, Asia, and Africa) and New World CL (Latin America).…”
Section: Introductionmentioning
confidence: 99%